KURIKULUM MENURUT IBNU KHALDUN - Salsabila, Rara Bilqis; Assegaf , Abd. Rachman (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
Curriculum is the core of the educational process as it determines the direction, objectives, and quality of learning outcomes. The educational thought of Ibn Khaldun is worth re-examining, as he emphasized the importance of balancing religious knowledge (naqliyah) and rational knowledge (aqliyah) as the foundation for developing holistic human beings. This study aims to explore Ibn Khaldun’s concept of curriculum, the teaching methods he proposed, and their relevance to modern education. This research employs a qualitative approach using library research and content analysis of Ibn Khaldun’s seminal work, al-Muqaddimah, along with relevant secondary sources. The findings reveal that Ibn Khaldun’s curriculum goes beyond rote memorization, prioritizing deep understanding, teacher’s exemplary role, and gradual learning from basic to advanced levels. He believed that education should produce individuals who are both faithful and knowledgeable, capable of contributing to society. In conclusion, Ibn Khaldun’s educational thought remains relevant today, aligning with modern educational principles that emphasize knowledge integration, character formation, and the development of critical thinking skills. Thus, his ideas can serve as a valuable inspiration for formulating both Islamic and general education curricula in the era of globalization.